Multimolecular tracers of terrestrial carbon transfer across the pan-Arctic: 14C characteristics of sedimentary carbon components and their environmental controls; Global Biogeochemical Cycles; Vol. 29, iss. 11 - Feng X.; Gustafsson O.; Holmes R. M.; Vonk J. E.; van Dongen B. E.; Semiletov I. P. Igor Petrovich; Dudarev O. V. Oleg Viktorovich; Yunker М. B.; Macdonald R. W.; Wacker L.; Montlucon D. B.; Eglinton T. I. (2015, 2015)
Title screen